Inflammatory chemokine eotaxin-1 is correlated with age in heroin dependent patients under methadone maintenance therapy. (1st February 2018) - Kuo, Hsiang-Wei; Liu, Tung-Hsia; Tsou, Hsiao-Hui; Hsu, Ya-Ting; Wang, Sheng-Chang; Fang, Chiu-Ping; Liu, Chia-Chen; Chen, Andrew C.H.; Liu, Yu-Li
Highlights: CCL11 could be an indicator for neurodegeneration. CCL11 showed the strongest correlation with age by a cut-off at 45 years old. Patients of 45 years old or older had higher plasma CCL11 and FGF-2 levels. CCL11 involving neurotoxicity in heroin dependent patients under MMT. Abstract: Background: Degeneration of central neurons and fibers has been observed in postmortem brains of heroin dependent patients. However, there are no biomarkers to predict the severity of neurodegeneration related to heroin dependence. A correlation has been reported between inflammatory C-C motif chemokine ligand 11 (CCL11, or eotaxin-1) and neurodegeneration in Alzheimer's disease. Methods: Three-hundred-forty-four heroin dependent, Taiwanese patients under methadone maintenance treatment (MMT) were included with clinical assessment and genomics information. Eighty-seven normal control subjects were also recruited for comparison. Results: Using receiver operating characteristics curve analyses, CCL11 showed the strongest sensitivity and specificity in correlation with age by a cut-off at 45 years (AUC = 0.69, P  < 0.0001) in MMT patients, but not normal controls. Patients 45 years of age or older had significantly higher plasma levels of CCL11, fibroblast growth factor 2 (FGF-2), nicotine metabolite cotinine, and a longer duration of addiction. Plasma level of CCL11 was correlated with that of FGF-2 (partial r 2  = 0.24, P  < 0.0001). Carriers with the mutant allele of rs1129844, a functional single nucleotide polymorphism (Ala23Thr) in the CCL11 gene, showed a higher plasma level of Aß42, ratio of Aß42/Aß40, and insomnia side effect symptom score than the GG genotype carriers among MMT responders with morphine-negative urine results. Conclusions: The results suggest possible novel mechanisms mediated through CCL11 involving neurotoxicity in heroin dependent patients.